(untitled) (Journal of Governance and Development (JGD), 2025)
This research aimed to present a comprehensive bibliometric analysis of the scholarly landscape on organizational inclusiveness across disciplines. Thematic structures, intellectual networks, and geographic trends were mapped using VOSviewer considering 1,308 open-access articles indexed in Scopus from 1988 to 2025. The results showed that there was a sharp increase in publications after 2020 driven by technological advancements, market pressures, and a growing global commitment to diversity, equity, and inclusion (DEI). The five main thematic clusters identified were inclusive pedagogy, social justice, organizational governance, digital transformation, and mental well-being. The analysis also reported the dominance of research from Global North and the low contribution from the South. Several research focused on the corporate and education sectors, with limited attention to non-profit, community, and value-based organizations. A future analysis agenda was proposed to address conceptual fragmentation, geographic disparities, and developing issues, including intersectionality, belonging, and institutional transformation. The results contributed to building a more inclusive and contextual understanding of organizational practices.